Characterization of nanocrystalline cellulose isolated from empty fruit bunch using acid hydrolysis - Gan, P.G. (Trans Tech Publications Ltd, 2017)
In recent years, there has been a great interest in the production of nanocrystalline cellulose (NCC) due to its excellent properties. In this study, empty fruit bunch (EFB) was used as the material for the production of NCC due to its high cellulose content, inexpensive and readily-available source. NCC was prepared using acid hydrolysis at 62 for 1 hours. The morphology of NCC was determined by Field Emission Scanning Electron Microscopy (FESEM). The size of NCC was less than 50 nm in width. The obtained NCC was also characterized by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). FTIR spectra analysis showed that hemicellulose and lignin were mostly removed from the EFB after bleaching and alkaline pre-treatment. XRD diffractograms revealed that EFB nanocellulose showed a crystallinity improvement of 24.3 compared to raw EFB cellulose. © 2017 Trans Tech Publications, Switzerland.